Adding Rotation to Translation: Percepts and Illusions. (September 2014) - Magnussen, Camilla M; Orbach, Harry S; Loffler, Gunter
This study investigated how the perception of a translating object is affected by rotation. Observers were asked to judge the motion and trajectory of objects that rotated around their centroid while linearly translating. The expected percept, consistent with the actual dynamics used to generate the movie sequences, is that of a translating and rotating object, akin to a tumbling rugby ball. Observers, however, do not always report this and, under certain circumstances, perceive the object to translate on an illusory curved trajectory, similar to a car driving on a curved road. The prevalence of veridical versus nonveridical percepts depends on a number of factors. First, if the object's orientation remains within a limited range relative to the axis of translation, the illusory, curved percept dominates. If the orientation, at any point of the movie sequence, differs sufficiently from the axis of translation, the percept switches to linear translation with rotation. The angle at which the switch occurs is dependent upon a number of factors that relate to an object's elongation and, with it, the prominence of its orientation. For an ellipse with an aspect ratio of 3, the switch occurs at approximately 45°. Higher aspect ratios increase the range; lower ratios decrease it. This applies similarly to rectangular shapes. A line is more likely to be perceived on a curved trajectory than an elongated rectangle, which, in turn, is more likely seen on a curved path than a square. This is largely independent of rotational and translational speeds. Measuring perceived directions of motion at different instants in time allows the shape of the perceived illusory curved path to be extrapolated. This results in a trajectory that is independent of object size and corresponds closely to the actual object orientation at different points during the movie sequence. The results provide evidence for a perceptual transition from an illusory curved trajectory to a veridical linear trajectory (with rotation) for the same object. Both are consistent with special real-world cases such as objects rotating around a centre outside of the object so that their orientation remains tangent to the trajectory (cheetahs running along a curve, sailboats) or objects tumbling along simple trajectories (a monkey spinning in air, spinning cars on ice). In certain cases, the former is an illusion.